Small Claims Court Based on An Agreement to Support Ease of Doing Business In Indonesia (Universitas Negeri Semarang, 2022)
The limit of material claim in the small claims court regulated in PERMA Number 4 of 2019 can be seen as a limitation towards the choice of forums for resolving disputes. Therefore, this research initiates a legal breakthrough that allows the limit of material claim to be deviated by agreement or contract. After analyzing the relevant legal sources, it can be concluded that the formation of a small claims court based on an agreement is in accordance with the principles of quick, simple, and affordable trial. In line with the utilitarian approach and economic analysis of law, it is expected that the expansion of the range of small claims court procedures will bring benefits to the community, especially incresing the ease of doing business in Indonesia. This idea does not violate the basic principles of a small claims court because it only changes the terms of a dispute that can be resolved by a small claims procedures, while the mechanism for examining the case still refers to the existing regulations. The formulation of the norm can be read:“The maximum value of the lawsuit is IDR 500,000,000.00 (five hundred million rupiah), unless otherwise agreed with a written agreement that expressly states that the dispute resolution chosen is a small claims court forum of which the material claims exceed the maximum limit regulated in PERMA Number 4 of 2019.”